Data Processing and Archive System for the Antarctic PANSY Rader - Koji, Nishimura; Masaki, Tsutsumi; Yoshihiro, Tomikawa; Toru, Sato; Taishi, Hashimoto; Masashi, Kohma; Kaoru, Sato (2017)
International workshop on sharing, citation and publication of scientific data across disciplines: Session 2: Database, Data System - Network & Administration Tue. 5 Dec./Lecture Room (4F, NIPR) conference object